2004
DOI: 10.1208/aapsj060325
|View full text |Cite
|
Sign up to set email alerts
|

Neural retina limits the nonviral gene transfer to retinal pigment epithelium in an in vitro bovine eye model

Abstract: We investigated the permeation of liposomal and polymeric gene delivery systems through neural retina into retinal pigment epithelium (RPE) and determined the roles of various factors in permeation and subsequent uptake of the delivery systems by RPE. Anterior parts and vitreous of fresh bovine eyes were removed. Retina was left intact or peeled away. Complexes of ethidium monoazide (EMA)-labeled plasmid DNA and cationic carriers (polyethyleneimine, poly-Llysine, DOTAP liposomes) were pipetted on the retina or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Unfortunately, in contrast to the situation in vitreous, we show in this study that a high pegylation degree of DOTAP DOPE lipoplexes does not improve their permeation through the neural retina. Our results confirm previous experiments by Pitkänen et al (33) who found that neural retina completely blocks nonpegylated lipoplexes. Their data indicated that the cationic charge of the penetrating substance is even more important than its size.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Unfortunately, in contrast to the situation in vitreous, we show in this study that a high pegylation degree of DOTAP DOPE lipoplexes does not improve their permeation through the neural retina. Our results confirm previous experiments by Pitkänen et al (33) who found that neural retina completely blocks nonpegylated lipoplexes. Their data indicated that the cationic charge of the penetrating substance is even more important than its size.…”
Section: Discussionsupporting
confidence: 93%
“…The eyes were kept at +9°C. The eyes were treated as previously described by Pitkänen et al (33) Briefly, after the eyes were cleaned of extra-ocular tissue and dipped in a 0.9% NaCl solution containing 1% penicillin/streptomycin (Gibco, Merelbeke, Belgium), they were opened circumferentially ±8 mm behind the limbus. The anterior tissues and the vitreous were separated gently from the neural retina.…”
Section: Manipulation Of Bovine Eyesmentioning
confidence: 99%
See 1 more Smart Citation
“…[68] Moreover, the inner and outer limiting membranes at the back of the eye present a tight barrier for gene delivery to the retinal tissues. [69] Pitkanen et al [72] demonstrated that the diffusion of PEI and PLL polyplexes through the neural retina was restricted by the inner limiting membrane, which contains laminin, collagen and several proteoglycans. Thus, additional surface modifications such a PEGylation may be required to overcome this barrier.…”
Section: Ocular Gene Therapymentioning
confidence: 99%
“…Cationic lipids and polymers are frequently used owing to binding and condensing of DNA and RNA to small particulates in the range of 100 nm. Despite their small size, the nanoparticulate systems have limited diffusion in the tissues, possibly due to the barriers placed by the vitreous and retina (74,75). This may be due to the steric hindrance and electrostatic interactions with ocular polyanions, such as hyaluronic acid and chondroitin sulfate.…”
Section: Non-viral Delivery Systems For Gene Therapymentioning
confidence: 99%